2017
DOI: 10.18632/oncotarget.19621
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in pre-miR146a and pre-miR499 are associated with systemic lupus erythematosus but not with rheumatoid arthritis or Graves’ disease in Mexican patients

Abstract: Recently, different microRNA (miRNA) gene polymorphisms have been evaluated in patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and Graves’ disease (GD). In the present study, we examined three single-nucleotide polymorphisms (SNPs) located in the pre-miR-146a (rs2910164G/C), pre-miR-196a-2 (rs11614913C/T), and pre-miR-499 (rs3746444A/G) genes. Our study population included 900 Mexican patients with RA, SLE, or GD, as well as 486 healthy control individuals with no family history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Consistently, the polymorphism rs3027898 in IRAK1, the target gene of miR-146a, is linked to RA in the Greek population (Chatzikyriakidou et al, 2010). However, follow-up studies showed inconsistent results in Polish (Bogunia-Kubik et al, 2016), Mexican (Aleman-Avila et al, 2017), and Chinese (Yang et al, 2011;Yang et al, 2012;Zhou et al, 2015b;Yang et al, 2017) populations. SNPs in other miRNAs were also tested in some studies, but their association with RA in other populations was not significant.…”
Section: Genetic Variations In Mirnas Explained Missing Susceptibilitmentioning
confidence: 90%
See 1 more Smart Citation
“…Consistently, the polymorphism rs3027898 in IRAK1, the target gene of miR-146a, is linked to RA in the Greek population (Chatzikyriakidou et al, 2010). However, follow-up studies showed inconsistent results in Polish (Bogunia-Kubik et al, 2016), Mexican (Aleman-Avila et al, 2017), and Chinese (Yang et al, 2011;Yang et al, 2012;Zhou et al, 2015b;Yang et al, 2017) populations. SNPs in other miRNAs were also tested in some studies, but their association with RA in other populations was not significant.…”
Section: Genetic Variations In Mirnas Explained Missing Susceptibilitmentioning
confidence: 90%
“…However, the reported genetic variants only explain <40% of the overall heritability of RA, leaving the majority of the heritability unaccounted for, thus suggesting the need for more studies that employ different approaches and populations in order to identify the missing causes. Association studies to miRNA loci provided the opportunity to identify RA-associated functional or causal variants within different populations, such as Chinese (Yang et al, 2011;Yang et al, 2012), Egyptian (El-Shal et al, 2013;Ayeldeen et al, 2018;), Polish (Bogunia-Kubik et al, 2016, Mexican (Aleman-Avila et al, 2017), and Iranian (Hashemi et al, 2013). The rs3746444 (20q11.22, A>G) polymorphism of miR-499, which is encoded by an intron of MYH7B, is significantly linked to RA risk, disease activity, and methotrexate (MTX) toxicity (Toraih et al, 2016); interestingly, the AA genotype shows higher disease activity and MTX toxicity than AG/GG genotypes (Fattah et al, 2018).…”
Section: Genetic Variations In Mirnas Explained Missing Susceptibilitmentioning
confidence: 99%
“…SNPs located in other miRNAs were also tested in some studies however the association is not quite significant. For example, miR-196a-2 (rs11614913C/T) and miR-499 (rs3746444A/G) were showed do not have significant association with RA in Mexico population (25). miR-146a (rs2910164) (20,31) and miR-499 (rs3746444) (20,30) were found do not have significant association with RA in Chinese.…”
mentioning
confidence: 89%
“…rs3027898 in IRAK1 which is the target gene of miR-146a was demonstrated associated RA in Greece population (29). However, follow-up studies showed inconsistent result in Poland (24), Mexico (25) and China (19,20,30,31) population. SNPs located in other miRNAs were also tested in some studies however the association is not quite significant.…”
mentioning
confidence: 99%
See 1 more Smart Citation